Impact‐induced chemical fractionation as inferred from hypervelocity impact experiments with silicate projectiles and metallic targets. (10th June 2018) - Ganino, Clément; Libourel, Guy; Nakamura, Akiko M.; Jacomet, Suzanne; Tottereau, Olivier; Michel, Patrick
Abstract: Hypervelocity impacts are common in the solar system, in particular during its early phases when primitive bodies of contrasted composition collided. Whether these objects are chemically modified during the impact process, and by what kind of processes, e.g., chemical mixing or gas–liquid–solid fractionation, are still pending questions. To address these issues, a set of impact experiments involving a multielemental doped phonolitic projectile and a metallic target was performed in a 3–7 km s −1 range of impact speeds which are typical of those occurring in the asteroid belt. For each run, both texture and chemistry of the crater and the ejecta population have been characterized. The results show that the melted projectiles largely cover the craters at all speeds, and that melted phonolitic materials are injected into fractures in the crater in the metallic target. Ejecta are generally quenched droplets of silicate impact melt containing metal beads. Some of these beads are extracted from the target, but we propose that some of the Fe metal beads are the result of reduction of FeO. A thin FeO‐SiO2 ‐rich condensate layer is found at the edge of the crater, suggesting that a limited amount of vapor formed and condensed. LA‐ICP‐MS analyses suggest, however, that within analytical uncertainties, no volatility‐controlled chemical fractionation of trace elements occurred in the ejecta. The main chemical fractionation during impact at such velocities and energies are the result of projectile‐target mixing.